Optoelectronic properties of cubic BxInyGa1−x−yN alloys matched to GaN for designing quantum well Lasers: First-principles study within mBJ exchange potential. (August 2015) - Assali, A.; Bouslama, M.; Abid, H.; Zerroug, S.; Ghaffour, M.; Saidi, F.; Bouzaiene, L.; Boulenouar, K.
Abstract: A Full-Potential Linearized Augmented Plane Wave calculation within density functional theory is performed to investigate the electronic and optical properties of cubic B x In y Ga1− x − y N alloys matched to GaN with low-Boron content ( x ≤0.187). The exchange-correlation potential is treated by the local density approximation (LDA) to calculate the structural properties. The band structure and density of states of these compounds are well predicted by modified Becke–Johnson (mBJ) exchange potential compared to LDA and generalized gradient approximation (GGA). Also, the optical properties are calculated by the mBJ exchange potential. The computed structural parameters are found to be in good agreement with experimental and theoretical data. The B x In y Ga1− x − y N alloy is expected to be lattice matched to GaN substrate for ( x =0.125, y =0.187). The incorporation of B and In into GaN substrate allows the reduction of the band gap energy. The real and imaginary parts of the dielectric function, refractive index, reflectivity and absorption coefficient are discussed on the basis on the energy band structure and the calculated density of states. The optical properties of B x In y Ga1− x − y N depend on the incorporated Boron content (with y =0.187). This means that B x In y Ga1− x − y N could constitute an active layer in single quantum well for the design of high-efficiency solar cells and optoelectronic devices as Laser Diodes operating in the UV spectral region.